Grievance-fueled sexual violence - Higgs, Tamsin; Darjee, Rajan; Davis, Michael R.; Carter, Adam J. (Frontiers in Psychology, 2023)
The grievance fueled violence paradigm encompasses various forms of targeted violence but has not yet been extended to the theoretical discussion of sexual violence. In this article, we argue that a wide range of sexual offenses can be usefully conceptualized as forms of grievance fueled violence. Indeed, our assertion that sexual violence is often grievance fueled is unoriginal. More than 40 years of research of sexual offending research has discussed the pseudosexual nature of much sexual offending, and themes of anger, power, and control – themes that draw clear parallels to the grievance fueled violence paradigm. Therefore, we consider the opportunities for theoretical and practical advancement through the merging of ideas and concepts from the two fields. We examine the scope of grievance in the context of understanding sexual violence, and we look to the role of grievance in the trajectory towards both sexual and nonsexual violence, as well as factors that might distinguish grievance fueled sexual from nonsexual violence. Finally, we discuss future research directions and make recommendations for clinical practice. Specifically, we suggest that grievance represents a promising treatment target where risk is identified for both sexual and nonsexual violence.